2004
DOI: 10.5194/angeo-22-3927-2004
|View full text |Cite
|
Sign up to set email alerts
|

Vertical velocity and turbulence aspects during Mistral events as observed by UHF wind profilers

Abstract: Abstract. The general purpose of this paper is to experimentally study mesoscale dynamical aspects of the Mistral in the coastal area located at the exit of the Rhône-valley Thanks to the use of the time evolution of the vertical profile of the horizontal wind vector, recent works have shown that the dynamics of the Mistral is highly dependent on the season because of the occurrence of specific synoptic patterns. In addition, during summer, thermal forcing leads to a combination of sea breeze with Mistral and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
(21 reference statements)
1
12
0
Order By: Relevance
“…13, 9b). In addition, the numerical field at 14:00 UTC displays a deepening of the ABL in the advected continental layer, supporting the results from Caccia et al (2004), who showed that the Mistral is raised up by the sea breeze near the coast.…”
Section: Iop2a -Offshore Advection Of the Ablsupporting
confidence: 75%
“…13, 9b). In addition, the numerical field at 14:00 UTC displays a deepening of the ABL in the advected continental layer, supporting the results from Caccia et al (2004), who showed that the Mistral is raised up by the sea breeze near the coast.…”
Section: Iop2a -Offshore Advection Of the Ablsupporting
confidence: 75%
“…In the central Mediterranean, the north-north-west cold and dry mistral (e.g. Jansá 1987;Jiang et al, 2003;Caccia et al, 2004;Corsmeier et al, 2005;Drobinski et al, 2005;Guénard et al, 2005Guénard et al, , 2006Lebeaupin Brossier and Drobinski, 2009) and its companion wind the tramontane (e.g. Drobinski et al, 2001) blows in the Gulf of Lion, occasionally up to the African coasts (Salameh et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The depth of the ABL increases westward from 500 to 1200 m with reflectivity values on the order of those observed on leg AF. Further to the west, a continental ABL is observed in the sheltered region in the lee of the Massif Central, with reflectivity values being significantly smaller than to the east of 43 • N. In this region, on leg CE, lidar measurements evidence the presence of gravity waves (at 2.2 km) inside the continental ABL and above, which are common features during Mistral events (Caccia et al, 2004;Drobinski et al, 2005). The vertical structure of the aerosol distribution in the atmosphere derived from LEANDRE-2 reflectivity is used to validate the CHIMERE simulations along the ARAT legs.…”
Section: Analysis At the Scale Of The Gulf Of Lionmentioning
confidence: 98%